High Pulsatile Load Decreases Arterial Stiffness: An ex vivo Study - Neutel, Cédric H. G.; Corradin, Giulia; Puylaert, Pauline; De Meyer, Guido R. Y.; Martinet, Wim; Guns, Pieter-Jan (Frontiers in Physiology, 2021)
Measuring arterial stiffness has recently gained a lot of interest because it is a strong predictor for cardiovascular events and all-cause mortality. However, assessing blood vessel stiffness is not easy and the in vivo measurements currently used provide only limited information. Ex vivo experiments allow for a more thorough investigation of (altered) arterial biomechanical properties. Such experiments can be performed either statically or dynamically, where the latter better corresponds to physiological conditions. In a dynamic setup, arterial segments oscillate between two predefined forces, mimicking the diastolic and systolic pressures from an in vivo setting. Consequently, these oscillations result in a pulsatile load (i.e. the pulse pressure). The importance of pulse pressure on the ex vivo measurement of arterial stiffness is not completely understood. Here, we demonstrate that pulsatile load modulates the overall stiffness of the aortic tissue in an ex vivo setup. More specifically, increasing pulsatile load softens the aortic tissue. Moreover, vascular smooth muscle cell (VSMC) function was affected by pulse pressure. VSMC contraction and basal tonus showed a dependence on the amplitude of the applied pulse pressure. In addition, two distinct regions of the aorta, namely the thoracic descending aorta and the abdominal infrarenal aorta, responded differently to changes in pulse pressure. Our data indicate that pulse pressure alters ex vivo measurements of arterial stiffness and should be considered as an important variable in future experiments. More research should be conducted in order to determine which biomechanical properties are affected due to changes in pulse pressure. The elucidation of the underlying pulse pressure-sensitive properties would improve our understanding of blood vessel biomechanics and could potentially yield new therapeutic insights.